A scoping review: Inquiring into the potency of response source credibility (RSC) towards enhancing crisis response strategies - Dominic, Egede Dominion; Mahamed, Mastura; Abdullah, Zulhamri; Hashim, Norliana (John Wiley and Sons Inc, 2024)
It is paramount to consider that organizations are not immune to crises. Communicating solutions to the cataclysm is indispensable when the response source is credible. Our article answers recent calls for more research into the efficacy of organizational response source credibility (RSC) during crises and maintaining reputation. RSC (trustworthiness) is one of the indispensable prerequisites for achieving effective result-oriented crisis response strategies and sustaining reputation in times of crisis. This article is a scoping review regarding the potential of RSC on crisis response strategies. The findings from this review raises the awareness of the crisis managers about the relevance of source credibility towards making crisis response effective and maintaining reputation during a crisis situation. This article provides insights to help crisis managers, institutions and policy-makers develop specific effective crisis response strategies using a credible source to boost stakeholders' confidence and maintain a good reputation during an organizational crisis. This article fills the gap in the crisis communication domain concerning the limited amount of information regarding factors that influence the efficacy of crisis response strategies. The originality of this article is validated by the systematic scoping review used.